2008
DOI: 10.5194/acp-8-5143-2008
|View full text |Cite
|
Sign up to set email alerts
|

First atmospheric observations of three chlorofluorocarbons

Abstract: Abstract.We report the first atmospheric observations of the Chlorofluorocarbons (CFCs) trifluorochloroethene, 3-chloropentafluoropropene and 4,4-dichlorohexafluoro-1-butene by means of Gas Chromatography with Electron Capture and Mass Spectrometric detection (GC-ECD-MS) in air samples taken at the Taunus Observatory operated by the University of Frankfurt (Main) and the Jungfraujoch High Altitude Research Station in Switzerland. These substances belong to a class of CFCs containing a double bond and are suspe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…To ensure internal consistency of our laboratory instrumentation, five air samples were analysed with the GC-TOFMS instrument (Obersteiner et al, 2016) and compared to our reference GC-QPMS (gas chromatograph coupled to a quadrupole mass spectrometer) which uses a similar preconcentration set-up (Hoker et al, 2015). Consistent results with the NOAA network (National Oceanic and Atmospheric Administration) have been demonstrated for the GC-QPMS in the past during the international halocarbons in air comparison experiment (IHALACE; Hall et al, 2014) intercomparison (Hall et al, 2014), but with a different sample preconcentration using liquid nitrogen (Brinckmann et al, 2012;Laube and Engel, 2008;Laube et al, 2010). The current laboratory set-up using the Stirling cooler-based preconcentration has been described by Hoker et al (2015) and has shown very consistent results with previous measurements.…”
Section: Laboratory Operation: Flask Sample Measurementsmentioning
confidence: 77%
“…To ensure internal consistency of our laboratory instrumentation, five air samples were analysed with the GC-TOFMS instrument (Obersteiner et al, 2016) and compared to our reference GC-QPMS (gas chromatograph coupled to a quadrupole mass spectrometer) which uses a similar preconcentration set-up (Hoker et al, 2015). Consistent results with the NOAA network (National Oceanic and Atmospheric Administration) have been demonstrated for the GC-QPMS in the past during the international halocarbons in air comparison experiment (IHALACE; Hall et al, 2014) intercomparison (Hall et al, 2014), but with a different sample preconcentration using liquid nitrogen (Brinckmann et al, 2012;Laube and Engel, 2008;Laube et al, 2010). The current laboratory set-up using the Stirling cooler-based preconcentration has been described by Hoker et al (2015) and has shown very consistent results with previous measurements.…”
Section: Laboratory Operation: Flask Sample Measurementsmentioning
confidence: 77%
“…An indoor sample taken at our institute contained no C 2 F 3 Cl and no CF 2 CFCF 2 Cl but a very small amount of CF 2 CFCF 2 CFCl 2 .The estimated mixing ratios for the six outdoor samples were in the lower and sub-ppt range and can be found in Table 1. The corresponding MS signals were reintegrated compared to Laube and Engel, 2008 by using an improved version of the integration software.…”
Section: Resultsmentioning
confidence: 99%
“…2. The GC QP terised and used before for studies by (Laube and Engel, 2008;Brinckmann et al, 2012) and showed consistent results in the international comparison IHALACE (International Halocarbons in Air Comparison Experiment) with the NOAA (National Oceanic and Atmospheric Administration) network (Hall et al, 2013). We discuss the use of TOF MS in atmospheric trace gas measurements, in particular for the detection and quantification of halocarbons, focusing on four substances: CFC-11, CFC-12, Halon-1211 and Iodomethane.…”
mentioning
confidence: 78%